STUDENTS’ MATHEMATICAL CREATIVE THINKING ABILITY VIEWED FROM SELF-REGULATED LEARNING IN LAPS-HEURISTIC LEARNING MODEL - Vena Agustina; Fashihah Fashihah; Puput Relitasari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Students’ Mathematical Creative Thinking Ability (MCTA) remains relatively low, particularly in generating original ideas and elaborated solutions, while the effect of Self-Regulated Learning (SRL) on MCTA has not been clearly identified in mathematics learning. This condition indicates the need for an instructional model that not only emphasizes problem-solving processes but also supports students’ independence and creativity in learning.Â This research aims to assess the effectiveness of the LAPS-Heuristic learning model on students’ MCTA and describe students' MCTA concerning their SRL. A mixed-methods approach utilizing a sequential explanatory design was employed in this study. Six subjects were selected from the eighth-grade class VIII A at State Junior High School 1 Tayu, chosen based on their SRL levels. The results indicate that (1) the LAPS-Heuristic learning model effectively on students' MCTA in the context of their SRL, and (2)Â Students classified as having high SRL were able to fulfill all MCTA indicators, namely fluency, flexibility, originality, and elaboration. In comparison, students with moderate SRL levels achieved three indicators, namely fluency, flexibility, and elaboration. Students with low SRL levels were only able to meet two indicators, namely fluency and flexibility. For students with low SRL who have not yet achieved proficiency in originality and elaboration,Â it is recommended that they engage in independent assignments and participate in peer teaching activities to foster their academic development.Â Kemampuan Berpikir Kreatif Matematis (KBKM) siswa masih tergolong rendah, khususnya dalam menghasilkan ide-ide yang orisinal dan solusi yang terelaborasi, sementara pengaruh Self-Regulated Learning (SRL) terhadap KBKM dalam pembelajaran matematika belum teridentifikasi secara jelas. Kondisi ini menunjukkan perlunya model pembelajaran yang tidak hanya menekankan pada proses pemecahan masalah, tetapi juga mendukung kemandirian dan kreativitas siswa dalam belajar.Penelitian ini bertujuan untuk mengkaji keefektifan pembelajaran LAPS-Heuristik terhadap Kemampuan Berpikir Kreatif Matematis (KBKM) dan mendeskripsikan KBKM siswa ditinjau dari SRL. Metode penelitian ini adalah mixed method dengan sequential explanatory. Enam subjek dipilih dari kelas VIII A SMP Negeri 1 Tayu berdasarkan tingkat SRL siswa. Hasil penelitian menunjukkan bahwa (1) model pembelajaran LAPS-Heuristik efektif terhadap KBKM siswaÂ ditinjau dari SRL, dan (2) siswa yang dikategorikan dengan SRL tinggi mampu memenuhi semua indikator KBKM: kelancaran, fleksibilitas, orisinalitas, dan elaborasi. Sebaliknya, siswa dengan tingkat SRL rata-rata mencapai tiga indikator: kelancaran, fleksibilitas, dan elaborasi. Sementara itu, siswa dengan SRL rendah hanya memenuhi indikator kelancaran dan fleksibilitas. Bagi siswa yang diidentifikasi memiliki SRL rendah yang belum mencapai indikator orisinalitas dan elaborasi, disarankan agar siswa terlibat dalam tugas mandiri dan berpartisipasi dalam kegiatan peer teaching untuk mendorong perkembangan akademis siswa.Â